2016
DOI: 10.3390/en9050359
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of Integrating First and Second-Generation Ethanol Production Using Filamentous Fungi: An Industrial Case Study

Abstract: Abstract:The 2nd generation plants producing ethanol from lignocelluloses demand risky and high investment costs. This paper presents the energy-and economical evaluations for integrating lignocellulose in current 1st generation dry mill ethanol processes, using filamentous fungi. Dry mills use grains and have mills, liquefactions, saccharifications, fermentation, and distillation to produce ethanol, while their stillage passes centrifugation, and evaporation to recycle the water and dry the cake and evaporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
2
16
0
1
Order By: Relevance
“…Also, the discovery of new raw materials (filamentous fungi), and the improvement of the process of obtaining bio-ethanol by integrating first-and second-generation ethanol production processes is described in [71] which reports a reduction of energy consumption by 2.5%, and an increase of ethanol production by 4%. Connolly et al [30] have detailed different methods for producing transport fuels, including ethanol and methanol, in terms of the resources, the conversion processes used, and the transport demands met.…”
Section: Bio-ethanol Productionmentioning
confidence: 99%
“…Also, the discovery of new raw materials (filamentous fungi), and the improvement of the process of obtaining bio-ethanol by integrating first-and second-generation ethanol production processes is described in [71] which reports a reduction of energy consumption by 2.5%, and an increase of ethanol production by 4%. Connolly et al [30] have detailed different methods for producing transport fuels, including ethanol and methanol, in terms of the resources, the conversion processes used, and the transport demands met.…”
Section: Bio-ethanol Productionmentioning
confidence: 99%
“…Thin stillage is generated in large quantities and the evaporation process to condense TS to CDS is the second most energy-intensive step in corn ethanol production after ethanol distillation. 21 By adding the fungal cultivation to thin stillage, the overall energy consumption was reduced to 18.9 GW, which is equivalent to a 2.5% energy reduction at the ethanol plant at the base scenario considered. 22 It was demonstrated that the energy reduction was mainly due to the evaporation costs and the subsequent drying operations for the concentrated syrup.…”
Section: Mycoalgae Biofilm Grown In the Thin Stillagementioning
confidence: 99%
“…22 It was demonstrated that the energy reduction was mainly due to the evaporation costs and the subsequent drying operations for the concentrated syrup. 21 Composition analysis of CDS shows that the majority is composed of yeast biomass as well as some soluble feedstock components. 23 Having TS/CDS as part of DDGS brings many issues to the animal feed materials.…”
Section: Mycoalgae Biofilm Grown In the Thin Stillagementioning
confidence: 99%
“…The techno-economy of the application of filamentous fungi in the treatment of industrial by-products has been considered in different research studies. Rajendran et al [40] studied the techno-economy of the integration of first and second-generation bioethanol production by the cultivation of filamentous fungi on by-product streams of stillage and wheat bran. They reported that although the integrated process imposed greater capital costs than only fungal cultivation on stillage, it could result in up to 48% increase in the net present value (NPV).…”
Section: Filamentous Fungi Cultivationmentioning
confidence: 99%